Registering Marriage in Pasuruan, East Java: The Interdependence of Role Between Penghulus and Modins in the Marriage Validation Process - Nurul Asiya Nadhifah; Mukhammad Nur Hadi; Umi Chaidaroh; Holilur Rohman; Habibi Zaman Riawan Ahmad (Journal of Islamic Law, 2026)
This article interrogates how Islamic marriage registration is governed in practice by examining the relational dynamics between the penghulu (marriage registrar) and the modin (village religious official) in Pasuruan Regency, East Java, within the broader project of bureaucratizing Islamic family law in Indonesia. Although state law formally centralizes marriage registration authority in the penghulu as the embodiment of legal-rational authority, empirical evidence reveals a layered socio-legal configuration shaped by limited state capacity, the enduring cultural legitimacy of the modin, and the practical demands of public service provision. Employing a socio-legal methodology, this field study draws on structured interviews with 19 informants across three sub-districts, non-participant observation, and analysis of relevant regulatory frameworks. The findings demonstrate that marriage administration operates through a pattern of structural interdependence between the penghulu and the modin, reflecting an interaction between legal-rational and traditional authority. Under conditions of bureaucratic constraint, the modin functions as a gatekeeper, a preliminary verifier, and an administrative intermediary, while the penghulu retains final authority over validation and formal marriage registration. This relational configuration not only sustains the operation of Islamic legal governance at the local level but also generates ongoing negotiations between formal legality and socially embedded legitimacy. The article argues that the bureaucratization of Islamic family law does not displace traditional authority; rather, it reconstitutes it within an interdependent governance framework. In doing so, the study contributes to contemporary scholarship on Islamic law and legal pluralism by demonstrating how legal-rational and traditional authority are mutually constituted within everyday administrative practice. [Artikel ini mengkaji bagaimana tata kelola pencatatan perkawinan Islam dijalankan dalam praktik dengan menelaah dinamika relasional antara penghulu dan modin di Kabupaten Pasuruan, Jawa Timur, dalam kerangka birokratisasi hukum keluarga Islam di Indonesia. Meskipun hukum negara secara formal memusatkan kewenangan pencatatan perkawinan pada penghulu sebagai representasi otoritas legal-rasional, realitas empiris memperlihatkan konfigurasi sosio-legal yang berlapis, dipengaruhi oleh keterbatasan kapasitas negara, kuatnya legitimasi kultural modin, serta tuntutan pragmatis pelayanan publik. Dengan menggunakan pendekatan sosio-legal, penelitian lapangan ini dilakukan di tiga kecamatan melalui wawancara terstruktur terhadap 19 informan, observasi non-partisipan, serta analisis terhadap kerangka regulasi yang relevan. Temuan penelitian menunjukkan bahwa administrasi perkawinan berjalan melalui pola ketergantungan struktural antara penghulu dan modin, yang merefleksikan interaksi antara otoritas legal-rasional dan otoritas tradisional. Dalam konteks keterbatasan birokratis, modin berfungsi sebagai gerbang awal, verifikator pertama, dan perantara administratif, sementara penghulu tetap memegang otoritas final dalam validasi dan pencatatan pernikahan resmi. Konfigurasi relasional ini tidak hanya menopang keberlangsungan tata kelola hukum Islam di tingkat lokal, tetapi juga memperlihatkan negosiasi berkelanjutan antara legalitas formal dan legitimasi sosial yang mengakar. Artikel ini berargumen bahwa birokratisasi hukum keluarga Islam tidak menyingkirkan otoritas tradisional, melainkan merekonstitusikannya dalam kerangka tata kelola yang bersifat interdependen. Dengan demikian, penelitian ini berkontribusi pada pengembangan kajian hukum Islam dan pluralisme hukum dengan menunjukkan bahwa otoritas legal-rasional dan tradisional dalam praktik administratif sehari-hari tidak bekerja secara terpisah, melainkan saling membentuk dan menguatkan.]